An Analysis of Euphemism in 2 Broke Girls - Yang, Xiaohua; Xu, Peiwen (Advances in Social Sciences Research Journal, 2015)
As a language phenomenon which widely exists in our human society, euphemism plays a crucial part in the process of language learning and social communication. Although the study of euphemism is not a new topic, the increasingly developing euphemism is still worth of being emphasized and analyzed. Then this thesis discusses euphemism in 2 Broke Girls from three aspects: how different people utilize different euphemism, main contents of euphemism, and expressional methods. What I have studied includes euphemism which was usually used before and which is prevalent now as well. My thesis analyzes language phenomenon and illustrates it with examples. I really hope my paper can give some enlightenment to English learners and help them to surmount the obstacle of comprehending euphemism and English culture.